Pengaruh Return On Asset Dan Earning Per Share Terhadap Harga Saham Sektor Pertambangan Yang Terdaftar Di Jakarta Islamic Index Periode 2016-2021 - Prakasa, Bayu; Mutia, Agustina; Subhan, Muhammad (Maisyatuna, 2023)
The purpose of conducting this research is to analyze and find out how the influence of return on assets and earnings per share has on mining sector stock prices listed on the Jakarta Islamic Index for the period 2016 – 2021. This research uses quantitative methods and panel data regression analysis methods. The samples used were 7 companies with a total of 6 years of data, namely 42 data, using a purposive sampling technique. The results showed that the variable return on assets partially has a significant effect on stock prices, while the earnings per share variable partially has no significant effect on stock prices. Simultaneously, the variables return on assets and earnings per share have a significant influence on the mining sector stock prices listed on the Jakarta Islamic Index for the period 2016–2021 with a coefficient of determination for this model of 93.61%.